Development and validation of the Attachment Relationship Inventory—Caregiver Perception 2–5 years (ARI‐CP 2–5): Psychometric structure, external validity, and norms. Issue 2 (17th January 2021) - Spruit, Anouk; Colonnesi, Cristina; Wissink, Inge; Uittenbogaard, Renée; Willems, Lucia; Stams, Geert‐Jan; Noom, Marc
ABSTRACT: There is a lack of instruments assessing child–caregiver attachment relationships in early childhood to be used in attachment‐based practice, in particular from a caregiver's perception, which is an important factor of clinical importance to take into account in parenting interventions targeting young children. Therefore, the 48‐item Attachment Relationship Inventory—Caregiver Perception 2–5 years (ARI‐CP 2–5) was developed. Survey data of 446 caregivers of 2‐ to 5‐year‐old children were collected, and a subsample of 83 caregivers participated in an observation study. Confirmatory factor analysis confirmed a four‐factor structure of secure, avoidant, ambivalent, and disorganized attachment relationship. Indications of configural, metric, and scalar invariance were found for caregivers' and children's sex, children's age, and population (clinical vs. general population). The four scales showed sufficient internal consistency and significant associations with children's psychopathology, caregivers' general attachment representations, caregivers' mind‐mindedness, and population type. Moreover, preliminary evidence for convergent validity with observational attachment measures was found. It is concluded that the ARI‐CP 2–5 is a valid instrument that can be used as part of the screening and assessment of insecure attachment relationships. RESUMEN: Hacen falta instrumentos que evalúen las relaciones de afectividad niño‐cuidador en la temprana niñez para ser usados en la práctica que se basa en la afectividad, en particular desde la perspectiva del cuidador, lo cual es un factor clave de importancia clínica para tomar en cuenta en las intervenciones de crianza que se enfocan en niños pequeños. Por tanto, se desarrolló el Inventario de la Relación Afectiva – Percepción del Cuidador 2–5 años, que consta de 48 aspectos (ARI‐CP 2–5). Se recogió información de encuesta de 446 cuidadores de niños de 2 a 5 años de edad, y un subgrupo muestra de 83 cuidadores participó en un estudio de observación. Los análisis de factores confirmatorios corroboraron una estructura de cuatro factores de la relación de afectividad que es segura, la que evita, la ambivalente y la desorganizada. Se encontraron indicaciones de invariabilidad en el aspecto configuracional, métrico y de escala en cuanto al género sexual de los cuidadores y del niño, la edad del niño, y la población (clínica y general). Las cuatro escalas mostraron una suficiente consistencia interna y asociaciones significativas con la sicopatología de los niños, las representaciones generales de afectividad del cuidador, la conciencia mental de los cuidadores, así como el tipo de población. Es más, se encontró una evidencia preliminar para la validez convergente con las medidas de afectividad de observación. Se concluye con que el ARI‐CP 2–5 es un instrumento válido que puede usarse como parte de la detección y evaluación de las relaciones de afectividad inseguras. RÉSUMÉ: Il y a un manque d'instruments évaluant les relations d'attachement enfant‐aidant naturel dans la petite enfance pouvant être utilisés dans une pratique basée sur l'attachement, en particulier sur la perception de l'aidant naturel, qui est un facteur important de l'importance clinique à prendre en compte dans les interventions de parentages ciblant les jeunes enfants. Par conséquent l'Inventaire de 48 articles de la Relation d'Attachement – Perception de l'Aidant Naturel 2–5 ans (abrégé en anglais ARI‐CP 2–5) a été développé. Les données de sondage de 446 aidants naturels d'enfants de 2 à 5 ans ont été recueillies et un sous‐échantillon de 83 aidants naturels ont participé à une étude d'observation. Une analyse factorielle confirmatoire a confirmé une structure à quatre facteurs de la relation d'attachement sécure, évitant, ambivalent et désorganisé. Des indications d'invariance configurale, métrique et scalaire ont été trouvées pour le sexe des aidants naturels et des enfants, l'âge des enfants, et la population (clinique par rapport à population générale). Les quatre échelles ont démontré une cohérence interne suffisante et des associations importantes avec la psychopathologie des enfants, les représentations de l'attachement générale des aidants naturels, l'esprit‐qualité mentale et le type de population. De plus une preuve préliminaire de validité convergente ave les mesures observationnelles d'attachement a été trouvée. Nous concluons que l'ARI‐CP 205 est un instrument valide qui peut être utilisé pour le dépistage et l'évaluation de relations d'attachement insécures. ZUSAMMENFASSUNG: Entwicklung und Validierung des Inventars für Bindungsbeziehung – Eltern‐ bzw. Betreuer_innenperspektive 2–5 Jahre (ARI‐CP 2–5): Psychometrische Struktur, externe Validität und Normen Es fehlen Instrumente zur Beurteilung der Bindungsbeziehungen zwischen Kleinkind und Bezugsperson, die in der bindungsbasierten Praxis verwendet werden können. Insbesondere fehlen hierbei Instrumente, die die Wahrnehmung der Bezugspersonen einschließen ‐ ein Faktor von großer klinischer Bedeutung, der bei Elterninterventionen für Kleinkinder berücksichtigt werden sollte. Aus diesem Grund wurde das 48‐Punkte‐Inventar für Bindungsbeziehung – Eltern‐ bzw. Betreuer_innenperspektive 2–5 Jahre (ARI‐CP 2–5) entwickelt. Von 446 Bezugspersonen 2‐5‐jähriger Kinder wurden Umfragedaten gesammelt und eine Teilstichprobe von 83 Bezugspersonen nahm an einer Beobachtungsstudie teil. Eine konfirmatorische Faktoranalyse ergab eine Vier‐Faktoren‐Struktur aus sicheren, vermeidenden, ambivalenten und unorganisierten Bindungsbeziehungen. Hinweise auf konfigurale, metrische und skalare Messinvarianz wurden für Geschlecht und Alter der Bezugspersonen und Kinder sowie für die Stichprobe (klinisch vs. allgemein) gefunden. Die vier Skalen wiesen ausreichende interne Konsistenz und signifikante Assoziationen mit der kindlichen Psychopathologie, den allgemeinen Bindungsrepräsentationen, dem Mind‐Mindedness der Bezugspersonen und der Art der Stichprobe auf. Darüber hinaus wurden vorläufige Belege für konvergente Validität mit beobachtenden Bindungsmaßen gefunden. Es wird der Schluss gezogen, dass der ARI‐CP 2–5 ein valides Instrument ist, das im Rahmen von Screenings und Beurteilungen unsicherer Bindungsbeziehungen verwendet werden kann. 抄録: 愛着関係調査票–2歳から5歳の養育者の認識 (ARI‐CP 2–5)の開発と検証:心理検 査構造、外部の妥当性と規範 幼児期に幼児―養育者の愛着関係を評価する方策が不足しており、幼児を対象と した子育て介入において臨床的に考慮すべき重要な要素である愛着、特に愛着に 対する養育者の認識に基づいた実践に活用できない。そこで、48項目の愛着関係 調査票‐2歳から5歳の養育者の認識 (ARI‐CP 2–5)が開発された。446人の2歳から 5歳の子どもの養育者の調査データが収集され、二次標本として83人の養育者が 観察研究に参加した。確認的因子分析で安全型、回避型、抵抗/両価型、混乱型 の愛着という4因子の構造を確認した。養育者と子どもの性別、子どもの年齢、 集団 (臨床と一般) のために構成の指標と測定基準、およびスカラー不変性が発 見された。4つのスケールは十分な内的整合性を示し、子どもの精神病理、養育 者の一般的な愛着表現、養育者のマインドマインドネス、母集団のタイプとの間 に有意な関連を示した。さらに観察に基づいた愛着の評価とともに収束性妥当性 のための予備的証拠が見つかった。ARI‐CP 2–5は、不安定型愛着関係のスクリー ニングと評価の一部として使用できる有効な手段であると結論付けられる。 摘要: 摘 要:目前缺乏可用于依恋实践的评估儿童早期看护者依恋关系的工具, 特别是从看护者的感知角度, 这是针对幼儿的养育干预措施中需要考虑的一个重要临床因素。因此, 编制了含括48题的依恋关系 – 2–5岁儿童看护者感知量表 (ARI‐CP 2–5)。收集了446名2–5岁儿童看护者的调查数据, 并以83名看护者子样本为被试进行观察研究。验证性因素分析证实了安全、回避、矛盾和无序依恋关系的四因素结构。在看护者和儿童性别、儿童年龄以及人群 (临床和一般人群) 中发现了构型、度量和标量不变性的迹象。四个量表显示出足够的内在一致性, 并与儿童的精神病理学、看护者的一般依恋表征、看护者的心智和人群类型显著相关。此外, 还发现了通过观察依恋措施聚合效度的初步证据。结论:ARI‐CP 2–5是一种有效的工具, 可用于不安全型依恋关系的部分筛选和评估。 ملخص: تطوير وتحقيق مقياس التعلق المرتبط بالعلاقات ‐ تصورات مقدم الرعاية 2–5 سنوات دراسة البنية السيكوميترية والصلاحية الخارجية والمعايير هناك نقص في الأدوات التي تقيِّم العلاقات بين الأطفال ومقدمي الرعاية في مرحلة الطفولة المبكرة لاستخدامها في الممارسة القائمة على التعلق، ولا سيما من منظور مقدم الرعاية، والذي يعتبر عامل مهم من العوامل ذات الأهمية الاكلينيكية التي ينبغي مراعاتها في التدخلات الوالدية التي تستهدف الأطفال الصغار. ولذلك تم تطوير قائمة فحص التعلق من 48 عنصر ‐ منظور مقدم الرعاية 2–5 سنوات (5‐CP 2‐ARI) وتم جمع بيانات استقصائية عن 446 من مقدمي الرعاية للأطفال الذين تبلغ أعمارهم سنتين إلى خمس سنوات، وشارك في دراسة الملاحظة عينة فرعية من 83 من مقدمي الرعاية. أكد تحليل العامل وجود أربعة عوامل تمثل بنية التعلق الآمن، والمتجنب، والمتناقض، والغير منظم. وأشارت النتائج إلى وجود مؤشرات لثوابت شكلية، وقياسية من حيث جنس مقدمي الرعاية والأطفال، وأعمار الأطفال، والتركيبة السكانية (العينة الإكلينيكية مقابل عامة السكان).وأظهرت المقاييس الأربعة اتساقًا داخليًا كافيًا وارتباطا إحصائياً مع الصحة النفسية للأطفال، والتصورات العامة للتعلق عندمقدمي الرعاية، والتصورات الذهنية لمقدمي الرعاية، ونوع السكان. وعلاوة على ذلك، وُجد دليل أولي على الصلاحية المتقاربة لمقاييس التعلق القائمة على الملاحظة. وتخلص الدراسةإلى أن مقياس (5‐CP 2‐ARI) يعتبر أداة صالحة يمكن استخدامها كجزء من فحص وتقييم علاقات التعلق غير الآمنة .